Indonesia PENYERTAAN MODAL USAHA PEMBERDAYAAN MELALUI PEMBUATAN USAHA WARUNG “PECEL, JUS, DAN ANEKA MINUMAN (MAE SARINAH)” - Nazaliah Yusma Zahrani; Azmi, Dhiyaa; Rafa Maritza (Fisip UIN Sunan Gunung Djati Bandung, 2024)
This community service activity aims to empower underprivileged families, particularly focusing on women as heads of households, through business capital assistance. The study uses a Participatory Action Research (PAR) approach to identify and support needy families in lower-middle economic environments. The team selected three families, with Mrs. Sarinah chosen as the primary beneficiary due to her urgent needs. Mrs. Sarinah, a skilled cook, struggled to start a business due to insufficient capital and debt burdens. The program provided her with funds and resources to establish a small stall selling